Nhận thức về trách nhiệm công dân của sinh viên Việt Nam hiện nay - Lê , Anh Vũ (Tạp chí Giáo dục, 2024)
Students’ civic responsibility is an issue that needs addressing in the context of Vietnam’s developing digital economy based on science, technology and creative innovation. This research study was conducted using mixed research methods with data surveyed from 26,331 students and 75 in-depth interviews conducted in 6 regions across the country. The research results show that students tend to choose civic responsibilities related to themselves, family and country rather than those related to the community. We propose that it is necessary to continue to organize promotional activities so that students clearly understand the regulations on civic responsibilities in the 2020 Youth Law. In addition, Youth Union and Youth Association organizations need to strengthen ideological and lifestyle education with programs and activities suitable to the needs of students in the current context. This study is the basis for further research to propose a number of measures to improve the civic responsibility of Vietnamese students.